KUALITAS MENU, POLA MENU, KETERSEDIAAN ENERGI DAN ZAT GIZI PADA MENU MAKAN SAHUR DAN BERBUKA PUASA SELAMA RAMADHAN UNTUK PENGHUNI ASRAMA - Bachyar Bakri; Clarita Desi Saputri (Poltekkes Kemenkes Malang, 2019)
During the fasting month, the XY Kediri women dormitory held sahur meal and breaking fast for the residents of the dormitory which numbered 120 students with a school age range of 16 until 18 years. The type of food service is semi cafeteria with serving portion for almost all types of dishes is still below the recommended portion. The type of this research is observational and cross sectional research design. The research sample is a menu that is served as many as 5 menus for eating sahur and 5 menus for iftar. The types of data collected include menu quality, menu patterns, serving portions, and availability of energy and nutrients namely protein, fat, carbohydrates, iron, vitamin C. Data collection by filling out questionnaires and weighing the food served. The data obtained is then processed and analyzed descriptively then presented in the form of images and tables. The results of the study showed that the quality of food for sahur and breaking the fast, most of them were quite sufficient. For the menu pattern of the 10 menus presented there are only 2 menus or 20 percent which are categorized well. In observing the portion of food served in 10 menus the results of the average serving of food are not in accordance with the recommended standards. The availability of energy and nutrients for school age children does not meet the adequacy of energy and nutrients based on the recommended Nutritional Adequacy Rate according to age groups and is still in the deficit category. It is recommended to the food organizer to increase the budget for food costs for each child from the price of food Rp. 5,000.00 to Rp. 6,000.00, per meal, and paying more attention to a balanced menu pattern, serving portions of animal and vegetable dishes added to 50 grams each, vegetables added to 70 until 100 grams and fruit is expected to be at least 3 until 4 times each week.